Shariah Non Compliance Risks In Shared And Outsourced Services Of Takaful Operators - Sharifah Fairuz Syed Mohamad; Syed Othman Alhabshi; Ahcene Lahsasna (Global Academic Excellence (GAE), 2024)
Shared and outsourced services have been generally allowed by the regulator (Bank Negara Malaysia, BNM) for commercial expediency and enhanced competitiveness of takaful companies in Malaysia. While these objectives are acceptable, the requirement for takaful operators to be Shariah-compliant end to end is paramount. This study therefore aims to look at the processes involved to see whether there are any forms of Shariah non-compliance that needs to be mitigated. It uses qualitative approach through content analysis and interviews. In general, most of the processes are found to converge towards Shariah compliance. Findings from the study show that there are some Shariah non-compliance risks that could arise out of the shared or outsourced services. Firstly, there is a risk of non-compliance in the sharing of key persons who need to oversee both entities (takaful and insurance). Secondly, there could also be risks in the structure of promoting products through the same office or branches which could also lead to reputational risks. Several parameters are suggested to assist risk identification and mitigation processes in the shared or outsourced functions.